2016
DOI: 10.1038/srep33279
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a knock-in mouse model of the homozygous p.V37I variant in Gjb2

Abstract: The homozygous p.V37I variant in GJB2 is prevalent in East and Southeast Asians and may lead to mild-to-moderate hearing loss with reduced penetrance. To investigate the pathogenic mechanism underlying this variant, we generated a knock-in mouse model of homozygous p.V37I by an embryonic stem cell gene targeting method. Auditory brainstem response test showed that the knock-in mice developed progressive, mild-to-moderate hearing loss over the first 4–9 months. Overall no significant developmental and morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Functional studies performed in cells and mouse models support this conclusion [4042]. In consistent with previous reports [6, 12–14], we observed that the HL phenotypes associated with p.V37I varied by onset type, disease site, and degree of HL, implying that other causes, especially environmental factors, influence p.V37I-mediated onset of HL.…”
Section: Discussionsupporting
confidence: 92%
“…Functional studies performed in cells and mouse models support this conclusion [4042]. In consistent with previous reports [6, 12–14], we observed that the HL phenotypes associated with p.V37I varied by onset type, disease site, and degree of HL, implying that other causes, especially environmental factors, influence p.V37I-mediated onset of HL.…”
Section: Discussionsupporting
confidence: 92%
“…The homozygous p.V37I variant in GJB2 is prevalent in East and Southeast Asians and may lead to a broad spectrum of hearing phenotypes from mild-to-moderate hearing loss with reduced penetrance to profound hearing loss. The homozygous p.V37I knockin mice developed progressive, mild-to-moderate hearing loss over the first 4-9 months which modeled the hearing phenotype of the human patients, and confocal immunostaining and electron microscopic scanning revealed minor loss of the outer hair cells [21]. Thus, we regard it as likely pathogenic variants.…”
Section: Variants Classification and Evaluationmentioning
confidence: 84%
“…Propidium iodide dye transfer was impaired in GJB2 c.109G>A transfected HEK293T cells 29 . Homozygous knock-in mouse model of c.109G>A in Gjb2 was reported to have progressive mild hearing loss, more pronounced at higher sound frequencies 30 . However, because the codon for p.Val37 in mouse (GTG) was different from that in human (GTT), c.109G>A in mouse would translate into p.Val37Met, it was not counted towards strong functional evidence.…”
Section: Functional Evidencementioning
confidence: 99%